Integrative health care model for climacteric stage women: design of the intervention - Pérez-Cuevas Ricardo; Infante Claudia; Espinosa-Alarcón Patricia; Flores-Hernández Sergio; Doubova Svetlana V (BMC, 2011)
Abstract Background Climacteric stage women experience significant biological, psychological and social changes. With demographic changes being observed in the growing number of climacteric stage women in Mexico, it is important to improve their knowledge about the climacteric stage and its potential associated problems, encourage their participation in screening programs, and promote the acquisition of healthy lifestyles. At Mexican health care institutions the predominant health care model for climacteric stage women has a biomedical perspective. Medical doctors provide mostly curative services and have limited support from other health professionals. This study aims to design an integrative health care model (IHCM: bio-psycho-social, multidisciplinary and women-centered) applicable in primary care services aimed at climacteric stage women. Methods/Design We present the design, inclusion criteria and detailed description of an IHCM. The IHCM consists of collaborative and coordinated provision of services by a health team, which is involves a family doctor, nurse, psychologist, and the woman herself. The health team promotes the empowerment of women through individual and group counseling on the climacteric stage and health related self-care. The intervention lasts three months followed by a three-month follow-up period to evaluate the effectiveness of the model. The effectiveness of the model will be evaluated through the following aspects: health-related quality of life (HR-QoL), empowerment, self-efficacy and knowledge regarding the climacteric stage and health-related self-care activities, use of screening services, and improvement in lifestyles (regular leisure time physical activity and healthy diet). Discussion Participation in preventive activities should be encouraged among women in Mexico. Designing and evaluating the effectiveness of an integrative health care model for women at the climacteric stage, based on the empowerment approach and focus on health-related self-care to improve their HR-QoL is pertinent for current health conditions of this age group. Trial registration The study is registered at the ClinicalTrials.gov (NCT01272115).